A new species of Hyponephele Muschamp, 1915 from Tajikistan (Lepidoptera: Satyridae) - Korb, Stanislav K. (Zootaxa, 2015)
Hyponephele Muschamp, 1915 is a Palaearctic genus comprising 39 species (Eckweiler, Bozano, 2011), with most distributed in the Central Asiatic region. During the course of faunistic studies on the butterflies of Tajikistan, a new member of this genus was found; it is described herein as new. It is closely related and sympatric to H. hilaris (Staudinger, 1886) so compared to this one.